MENINGKATKAN PEMAHAMAN SISWA PADA MATERI TERMOKIMIA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY - Maira Aprialisa; Mahdian Mahdian (Universitas Lambung Mangkurat, 2010)
Abstract: The research on thermochemistry class using cooperative learning model types of “two stay two stray” method was conducted. This study aims to find out students 'improvement, affective skills, student’s activities and responses on “two stay two stray” method. This research used class-action-research design with 2 cycles. Subjects were A class of eleventh grade students of 5’s Senior High School Banjarmasin. Totally, there were 34 students involved on this study. Data was collected by using achievement test, questionnaires, and observations. Subsequently, data were analyzed by using percentation technique. The result showed that by using “two stay two stray” method, student’s achievments on thermochemistry improved by 17,98%. On average, student’s outcomes increased from 65,33% on the first cycle to 83,31% on the second cycle. Affective assessment pointed out that the affective skills of students were in good category (85,54%). Students gave positive responds to the model by 89,12%. From the first to the second cycle, student’s activities in the group improved.Key words: cooperative learning, two stay two stray method, thermochemistry.